(untitled) - A.F. Helene; P.L. Ribeiro (Brazilian Journal of Medical and Biological Research, 2013)
The growth of the Brazilian economy in recent years has created an atmosphere of optimism in various segments of Brazilian society, with several important international repercussions. In this paper, we analyze in detail how this economic growth is reflected in investments in science and technology made by major academic funding agencies. As a result, we observed a discrepancy in the growth of funding input and the growth of the Brazilian gross domestic product. This fact associated with an increased academic output entails negative consequences for the system. This may be a symptom of an academic community not fully understood by society and vice versa. Finally, we believe that a long-lasting important change in investment policy in science is necessary in order to ensure financial security for the academic system as a whole.